2020
DOI: 10.3390/ijerph17186567
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity and Sedentary Lifestyle in University Students: Changes during Confinement Due to the COVID-19 Pandemic

Abstract: Regular physical activity is related to many factors in a university student’s environment. The coronavirus pandemic and the resulting lockdown have restricted many elements of our environment. The aim of this study was to evaluate students’ physical activity and sedentary behaviour at two points in time: before and during the coronavirus lockdown. As a secondary aim, we also wanted to look at changes resulting from other factors (alcohol, tobacco, diet, stages of change, symptoms of anxiety/depression and soc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

33
349
11
43

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 393 publications
(436 citation statements)
references
References 39 publications
(39 reference statements)
33
349
11
43
Order By: Relevance
“…Nine out of the ten studies included in the systematic review showed significant decreases in PA levels during lockdown, both in questionnaires as accelerometers. Surprisingly, one study (Romero-Blanco et al, 2020 ) showed significant increases in PA levels among university students during lockdown. Romero-Blanco et al ( 2020 ) showed that Health Sciences university students performed significantly higher minutes/week of total PA (+71.6%) and vigorous PA (+7.4%), both males (+ 83.3%) as females (+ 23.6%).…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…Nine out of the ten studies included in the systematic review showed significant decreases in PA levels during lockdown, both in questionnaires as accelerometers. Surprisingly, one study (Romero-Blanco et al, 2020 ) showed significant increases in PA levels among university students during lockdown. Romero-Blanco et al ( 2020 ) showed that Health Sciences university students performed significantly higher minutes/week of total PA (+71.6%) and vigorous PA (+7.4%), both males (+ 83.3%) as females (+ 23.6%).…”
Section: Resultsmentioning
confidence: 96%
“…Surprisingly, one study (Romero-Blanco et al, 2020 ) showed significant increases in PA levels among university students during lockdown. Romero-Blanco et al ( 2020 ) showed that Health Sciences university students performed significantly higher minutes/week of total PA (+71.6%) and vigorous PA (+7.4%), both males (+ 83.3%) as females (+ 23.6%). On the other hand, Sañudo et al ( 2020 ) showed an objective reduction in PA with 67.7% fewer steps per day during the lockdown.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Gallo et al [8] investigated the impact of isolation measures on energy intake and physical activity levels in Australian university students, reporting a reduction in physical exercise levels, and an increase in energy intake and snacking frequency. Interestingly, Romero-Blanco et al [29] reported that-during home-confinement in Spain-university students that adopted a Mediterranean diet, also spent more time doing physical exercise. Ingram et al [30] investigated the changes in health behaviours related to negative mood states in a sample of about four hundred adults during the COVID-19 quarantine in the UK, reporting changes in diet, sleep quality, physical activity levels and poorer mental health.…”
Section: The Covid-19 Contextmentioning
confidence: 99%
“…Jayawardene et al [47] also highlighted that exercise could favour fruit and vegetable consumption in young adulthood. Romero-Blanco et al [29] conducted a study among university students during home-confinement due to COVID-19 in Spain, and evidenced a positive correlation between a Mediterranean diet (known to be rich in fruit and vegetables) and physical exercise. Physical exercise and healthy food choices seem to facilitate each other, via improved self-regulatory strategies and intentions (e.g., planning to perform physical exercise), indicating potential transfer effects between these behaviours [19,47,48].…”
Section: Effect Of Exercise On Nutritionmentioning
confidence: 99%